Implications of Technical and Vocational Education and Training (TVET) on economic development and employment prospects in Palestine - Nazzal, Mahmoud Mohamed; Akmal, Suriati; Mohamed Ahmed, Sara Salih; Bakar, Ahmad Zaki; Doheir, Mohamed A. S.; Safei, Su'aidi; Mohd Yaacob, Noorayisahbe (2024)
This paper aims to explore the vital role of Technical and Vocational Education and Training (TVET) in promoting economic development and enhancing employment prospects in Palestine. a descriptive-analytical approach was utilized to facilitate the analysis of the current state of TVET in Palestine and to study the main requirements for its development to further prepare for the job market armed with the knowledge needed. Secondary sources were used in the research such as books, academic journals, publications, reports, and periodic statistics. The research evaluates how TVET programs can bridge the gap between education and labor market demands. The study draws comparisons from successful international models like Germany, Malaysia, and China, highlighting how Palestine can adapt these frameworks to its unique socio-economic environment. The research suggests that TVET is a crucial driver in reducing unemployment, fostering economic growth, and equipping the Palestinian workforce with the competencies and capabilities needed to flourish in a modern economy.